Porcine model of a complicated skin and soft tissue infection caused by Pseudomonas aeruginosa - Lipovy, Bretislav; Vacek, Lukas; Kleknerova, Dominika Polastik; Jeklova, Edita; Liskova, Lenka; Holoubek, Jakub; Matyskova, Dominika; Ruzicka, Filip (Veterinarni medicina, 2024)
Pseudomonas aeruginosa poses a significant threat to both immunocompetent and immunocompromised individuals, often resulting in life-threatening infections. With increasing antimicrobial resistance, novel therapeutic strategies are urgently needed. Although animal models are crucial for preclinical studies, limited data are available for porcine models, more specifically for P. aeruginosa complicated skin and soft tissue infections (cSSTIs). This study presents a novel porcine model inducing and sustaining cSSTI for 14 days. Six pigs (120 wounds) were used for the development of infections, and within this group, two pigs (40 wounds) were used to evaluate the progression of the cSSTI infection. The model demonstrated bacterial loads of more than 107 CFU/gram of tissue or higher. The cSSTI fully developed within three days and remained well above these levels until day 14 post-infection. Due to the immunocompetence of this model, all the immunological processes associated with the response to the presence of infection and the wound healing process are preserved.
Keywords: ESKAPE pathogen; model development; pig; wound